Study of mortality trends & pattern in a tertiary care hospital in Kerala, South India - Ashwathy, A; Pramodkumar, G N; Undi, Malatesh; Prathvimraj , B U; Bakkannavar, Shankar M; Roopa Urs, A N; Srinivas, Vani (Journal of Indian Academy of Forensic Medicine, 2021)
Mortality statistics are essential for the meaningful planning and allocation of resources for healthcare. It has been observed that in India,  up-to- date, precise and reliable data regarding mortality patterns especially in the rural areas is inadequate or not properly documented.  Data regarding mortality is often not analyzed and converted into a suitable information to be useful in knowing the common causes for  death in specific and general populations. The mortality pattern at a Tertiary Care Hospital in Kerala from 2014-2018 and the  sociodemographic characters associated with it were studied. The details from the case sheets were obtained and analyzed using  descriptive methods. The total number of deaths recorded were 934, out of which, the maximum number of deaths has occurred in the  elderly population (Above 60 Years). 11 cases are of infant deaths. The major cause for infant mortality was found to be preterm and  extreme preterm birth. 576 deaths (61.6%) were males. Most number of deaths were due to Cardiovascular Causes (39.6%) followed by  Malignancy (12.7%) and respiratory diseases (12.4%). Out of the 934 cases of deaths, 310 patients belonged to rural areas (33.1%).  During the study it was noticed that the cause of death has been entered incompletely in many cases. Training of doctors & MRD faculty  with respect to cause of death writing and ICD classification according to system wise has to be done periodically for better  documentation which will help in future for data collection and easy analysis of the trends in disease and mortality.
Keywords: Mortality pattern; Epidemiology; Cause of Death; Hospital records